Who is Maud Dixon? : [large type] a novel - Andrews, Alexandra (Thorndike Press Large Print Thriller, Adventure and Suspense, 2021)
Florence Darrow is a low-level publishing employee who believes that she's destined to be a famous writer. When she stumbles into a job the assistant to the brilliant, enigmatic novelist known as Maud Dixon -- whose true identity is a secret -- it appears that the universe is finally providing Florence's big chance. The arrangement seems perfect. Maud Dixon (whose real name, Florence discovers, is Helen Wilcox) can be prickly, but she is full of pointed wisdom -- not only on how to write, but also on how to live. Florence quickly falls under Helen's spell and eagerly accompanies her to Morocco, where Helen's new novel is set. Amidst the colorful streets of Marrakesh and the wind-swept beaches of the coast, Florence's life at last feels interesting enough to inspire a novel of her own. But when Florence wakes up in the hospital after a terrible car accident, with no memory of the previous night -- and no sign of Helen -- she's tempted to take a shortcut. Instead of hiding in Helen's shadow, why not upgrade into Helen's life? Not to mention her bestselling pseudonym... Taut, twisty, and viciously entertaining, Who is Maud Dixon is a stylish psychological thriller about how far into the darkness you're willing to go to claim the life you always wanted.